The Effectiveness of Teaching Factory Management in Improving the Quality of Business Administration Graduates at Politeknik Negeri Manado - Makinggung, Juliet; Karambut, Christien; Winokan, Jemmry; Pangemanan, Kevin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to obtain policy recommendations for the effectiveness of TEFA management as an effort to improve the quality of graduates from the Business Administration Department at Politeknik Negeri Manado or Polimdo. This research is a field study with descriptive analysis. Data was collected through observation and interviews with several informants involved in the TEFA of the Business Administration Department. The results showed that TEFA has not yet identified industry standards and work procedures, and does not have a mature planning process where the TEFA team has not been established along with the functions and duties of each part. Similarly, the involvement of the industrial world in TEFA is still minimal. TEFA has not been socialized to all internal elements and external parties such as the community and industry. The impact of this is that TEFA is less effective in improving the quality of graduates from the Business Administration Department.